Factors that contributing price adaptation at Hotel Seri Malaysia Johor Bahru / Amirah Rahmat - Rahmat, Amirah (Faculty of Business and Management, 2010)
The price matrix is setting by the headquarter based on the market movement, buying power, economic condition and market trends. There are also several factors that contributing price adaptation. This study will reveal on what type of factors that contribute to the price adaptation. The objective of this study is to know the level of efficiency in price adaptation of Seri Malaysia Hotel Johor Bahru, to determine the relationship between factors towards price adaptation, to determine the most influence factors that give impact o price adaptation, to determine the correlation between factors and price adaptation and to identify the recommendations to improve the price adaptation.